Fetal Release of Copeptin in Response to Maternal Oxytocin Administration: A Randomized Controlled Trial. Issue 4 (October 2016) - Wellmann, Sven; Koslowski, Andrea; Spanaus, Katharina; Zimmermann, Roland; Burkhardt, Tilo
Abstract : OBJECTIVE: To test whether an oxytocin challenge test raises neonatal levels of copeptin, the C-terminal portion of proarginine vasopressin, a sensitive stress marker elevated in neonates born by vaginal delivery as opposed to elective cesarean delivery. METHODS: In a randomized controlled trial in women with a singleton pregnancy undergoing elective cesarean delivery at greater than 36 weeks of gestation and no contractions or rupture of membranes, we compared arterial umbilical cord plasma concentrations of copeptin between neonates exposed to an oxytocin challenge test before elective cesarean delivery and those administered saline infusion (placebo group). Women randomized to an oxytocin challenge test received 5 international units/500 mL oxytocin Ringer lactate infused at a rate of 12 mL/h and doubled every 10 minutes until it induced three uterine contractions per 10-minute interval, at which point it was discontinued. Neonatal copeptin levels were the primary endpoint. Secondary endpoints included biochemical and physiologic parameters of fetal and maternal well-being. RESULTS: From January 2012 to October 2012 and from September 2013 to January 2015, 78 women underwent an oxytocin challenge test and 78 placebo infusion, of whom 12 and 11, respectively, were excluded as a result of insufficient blood sample volume for analysis. Umbilical cord plasma copeptin levels [median (range)] were higher in neonates who underwent an oxytocin challenge test than those who underwent placebo infusion: 22.2 (3.22–2, 319) compared with 7.39 (2.5–344.6) pmol/L ( P <.001). There were no statistically significant differences between the two groups in secondary outcomes. CONCLUSION: Oxytocin challenge test-induced contractions before elective cesarean delivery trigger fetal copeptin release. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, https://clinicaltrials.gov, NCT01962701. Abstract : Uterine contractions in response to oxytocin challenge before elective cesarean delivery increase umbilical cord blood copeptin levels.